Preoperative Serum Human Epididymis Protein 4 Levels in Early Stage Endometrial Cancer: A Prospective Study. - Fanfani, Francesco; Restaino, Stefano; Cicogna, Stefania; Petrillo, Marco; Montico, Marcella; Perrone, Emanuele; Radillo, Oriano; De Leo, Rossella; Ceccarello, Matteo; Scambia, Giovanni; Ricci, Giuseppe (Int J Gynecol Cancer, 2017)
OBJECTIVE: The aim of the study was to evaluate the prognostic value of human epididymis protein 4 (HE4) and cancer antigen 125 markers with pathological prognostic factor to complete the preoperative clinical panel and help the treatment planning. METHODS: This prospective multicenter study was conducted in 2 gynecologic oncology centers between 2012 and 2014 (Institute for Maternal and Child Health IRCCS Burlo Garofolo in Trieste and Catholic University of the Sacred Heart in Rome, Italy). We enrolled 153 patients diagnosed with clinical early (International Federation of Gynecology and Obstetrics stages I-II) type I endometrial cancer. RESULTS: Human epididymis protein 4 levels seemed to be strictly related to age (P < 0.001) and menopausal status (P < 0.002). Compared with myometrial invasion (MI), the HE4 values were significantly higher in case of invasion of greater than 50% of the thickness: MI of greater than 50%, median of 94.85 pmol/L (38.3-820.8 pmol/L), versus MI of less than 50%, median of 65.65 pmol/L (25.1-360.2 pmol/L), (P < 0.001). The HE4 levels increase significantly with increasing tumor size: diameter of larger than 2 cm, median of 86.9 pmol/L (35.8-820.8 pmol/L), versus diameter of smaller than 2 cm, median of 52.2 pmol/L (33.3-146.8 pmol/L), (P < 0.001). In our population, HE4 did not correlate with the histological grade, endometrial cancer type I versus type II (P = 0.86), the lymphovascular infiltration (P = 0.12), and the cervical invasion (P = 0.6). We established a new variable, considering 3 high-risk tumor features: MI of greater than 50% and/or histological G3 and/or type II. Human epididymis protein 4 levels significantly increase in high-risk tumors (high risk HE4, 93.6 pmol/L vs low-medium risk, 65.5 pmol/L; P < 0.001). CONCLUSIONS: A preoperative HE4 evaluation could help stratify patients with deep invasion and/or metastatic disease and is correlated with other relevant prognostic factors to be considered to tailor an adequate surgical strategy.
Keywords: Adult; Aged; Aged, 80 and over; Biomarkers, Tumor; Endometrial Neoplasms; Female; Humans; Middle Aged; Neoplasm Staging; Preoperative Care; Prognosis; Prospective Studies; Proteins